MANAJEMEN KUALITAS PENDIDIKAN DI MADRASAH IBTIDAIYAH AL-HUSNA CILEDUG KOTA TANGERANG TAHUN 2021 - mas - tiaroh; Imam Mashud (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2021)
Management is a staple component that cannot be separated from Islamic educational institutions. Without management, the purpose of the institution cannot be realized optimally, effectively, and efficiently. Problems in educational institutions, usually dealing with the service to the customers of Islamic education. This research is a qualitative research aimed at knowing about the planning, organizing, implementation and evaluation of the quality management of Islamic education services in Madrasah Ibtidaiyah Al-Husna Ciledug Tangerang City.The results of this research show that the management planning of quality Islamic education services is conducted with a) to make the Madrasah Work Plan (MWP) which refers to the vision, mission, and the goal of Madrasah Ibtidaiyah Al-Husna Ciledug, b) Determine the needs of the customers of Islamic education through the increase of the Madrasah resources, c) Develop Islamic education programs according to customers ' expectations through the development of Islamic education programs that are poured in the curriculum of the Ibtidaiyah Al-Husna Ciledug. Organizing is done by implementing the quality standards of education and educationally through a) systematic, structured and directional activities, b) implementing harmonious and mutually co-operation, c) Division of tasks tailored to expertise. Implementation is done by placing personnel who are qualified especially in the activities of public relation that create programs such as relationship marketing, superior customer service, and monitoring the satisfaction of the Guardian students as an Islamic education customer in the Madrasah Ibtidaiyah Al-Husna Ciledug. Internal evaluation conducted in the monthly meeting and external evaluation of the input from the guardian of students who become education customers will be useful to improve the quality of education in the Madrasah Ibtidaiyah Al-Husna Ciledug Kota Tangerang.